Revealing potential of energy-saving behind emission reduction: A DEA-based empirical study. Issue 4 (10th June 2019) - Zhang, Douqing; Li, Mingjun; Ji, Xiang; Wu, Jie; Dong, Yilun
Abstract : Purpose: The purpose of this paper is to generate quantitative managerial insights for the improvement of the energy-saving potential and the coordinated development between economic growth and environmental protection. Design/methodology/approach: A novel data envelopment analysis (DEA) model, based on the classical DEA theory, is developed from the perspective of emission reduction. Findings: The empirical results indicate that China's overall environmental efficiency is low and that there is huge improvement space for energy saving. Under the concerns of emission reduction, the energy-saving potential of the central region exceeds that of both the eastern and western regions. With regard to water, electricity and gas consumption, the electricity-saving potential exceeds the potential for both water saving and gas saving. Originality/value: Previous studies rarely focused on the energy-saving potential, while considering environmental pollution. This paper applies a novel DEA method to evaluate the energy-saving potential of 30 Chinese provinces for 2015 with a focus on emission reduction concerns. Furthermore, both regional differences and energy type differences of the saving potential were analyzed.